DESAIN PUSAT PETERNAKAN DAN PENGOLAHAN HASIL TERNAK di MERAUKE DENGAN PENDEKATAN ARSITEKTUR HIJAU - Yashinta Irma Pratami Hematang; Agus Wahyu Saputro Rahmat; Atiza Nurhuzna (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2018)
The intended farm building complex is to be able to breed livestock and process livestock products so that they can meet the consumption needs of the people of Merauke City. The aim of the Center for Animal Husbandry and Processing of Livestock with the Green Architecture approach is to produce designs that minimize the adverse effects on the environment, nature and humans and produce a better and healthier place of life, which is carried out by utilizing energy and natural resources efficiently and optimal so that it does not adversely affect the surrounding environment. This study uses descriptive analysis method, where data and analysis obtained can be used as a reference in designing the Center for Animal Husbandry and Processing of Livestock Products in Merauke Regency. The results of this study are to design a center for animal husbandry and processing of livestock products with a site area of ​​37,500 m2. Existing facilities include; (1) Managing office, (2) Cage for livestock, (3) Office of cage officers, (4) Processing facilities, (5) Animal health rooms, (6) Slaughterhouses. Kata-kunci: Desain Bangunan., Peternakan., Hasil Ternak., Arsitektur Hijau.